Extent of Endoscopic Resection for Anterior Skull Base Tumors: An MRI-Based Volumetric Analysis - Koszewski, Ian J.; Avey, Gregory; Ahmed, Azam; Leonhard, Lucas; Hoffman, Matthew R.; McCulloch, Timothy M. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective To determine the volume of ventral skull base tumor removed following endoscopic endonasal (EEA) resection using MRI-based volumetric analysis and to evaluate the inter-rater reliability of such analysis.Design Retrospective case series.Setting Academic tertiary care hospital.Participants EEA patients November 2012 to August 2015.Main Outcome Measures Volumetric analysis of pre- and immediately postoperative MR imaging was performed independently by two investigators. The percentage of total tumor resected was evaluated according to resection goal and tumor type.Results A total of 39 patients underwent resection. Intraclass correlation coefficients between the raters were 0.9988 for preoperative and 0.9819 for postoperative images. Tumors (and average percentage removed) included 17 nonsecreting pituitary adenomas (95.3%), 8 secreting pituitary adenomas (86.2%), 4 meningiomas (81.6%), 3 olfactory neuroblastomas (100%), 2 craniopharyngiomas (100%), 1 large B–cell lymphoma (90.5%), 1 germ cell neoplasm (48.3), 1 benign fibrous connective tissue mass (93.4%), 1 epidermoid cyst (68.4%), and 1 chordoma (100%). For tumors treated with intent for gross total resection, 96.9 ± 4.8% was removed.Conclusion EEAs achieved tumor resection rates of ∼97% when total resection was attempted. The radiographic finding of residual tumor is of uncertain clinical significance. The volumetric analysis employed in this study demonstrated high inter-rater reliability and could facilitate further study.
Keywords: endoscopic skull base surgery; tumor volume; endonasal; extent of resection